Modulation of homomeric and heteromeric kainate receptors by the auxiliary subunit Neto1. (1st October 2013) - Fisher, Janet L.; Mott, David D.
Key points:   Kainate receptors (KARs) are a subtype of ionotropic glutamate receptors, which mediate excitatory neurotransmission. KARs can be regulated through assembly with the auxiliary subunits neuropilin and tolloid‐like 1 and 2 proteins (Neto1 and Neto2).   We characterized the effect of Neto1 on the glutamate sensitivity and desensitization properties of recombinant receptors containing different combinations of the five different KAR subunits (GluK1–GluK5).   We found that Neto1 reduces the onset of desensitization and speeds recovery from desensitization of both homomeric (K2) and heteromeric (with K4 or K5) receptors.   The largest impact of Neto1 was seen at sub‐maximal glutamate concentrations, suggesting that one functional role is to reduce desensitization in partially bound receptors.   Neto1 co‐assembly with neuronal KARs may alter the kinetics of the postsynaptic response, regulating the efficacy of glutamate neurotransmission. Abstract  The ionotropic glutamate receptors are primary mediators of fast excitatory neurotransmission, and their properties are determined both by their subunit composition and their association with auxiliary subunits. The neuropilin and tolloid‐like 1 and 2 proteins (Neto1 and Neto2) have been recently identified as auxiliary subunits for kainate‐type glutamate receptors. Heteromeric kainate receptors (KARs) can be assembled from varying combinations of low‐affinity (GluK1–GluK3) and high‐affinity (GluK4–GluK5) subunits. To better understand the functional impact of auxiliary subunits on KARs, we examined the effect of Neto1 on the responses of recombinant homomeric and heteromeric KARs to varying concentrations of glutamate. We found that co‐expression of Neto1 with homomeric GluK2 receptors had a small effect on sensitivity of the receptors to glutamate, but decreased the onset of desensitization while speeding recovery from desensitization. In the absence of Neto1, addition of GluK5 subunits to form GluK2/GluK5 heteromeric receptors slowed the onset of desensitization at low glutamate concentrations, compared with GluK2 homomers. Co‐expression of Neto1 with GluK2/GluK5 receptors further enhanced these effects, essentially eliminating desensitization at μm glutamate concentrations without altering the EC50 for activation by glutamate. In addition, a prominent rebound current was observed upon removal of the agonist. The rate of recovery from desensitization was increased to the same degree by Neto1 for both homomeric GluK2 and heteromeric GluK2/GluK5 receptors. Expression of Neto1 with GluK1/GluK5, GluK3/GluK5 or GluK2/GluK4 receptors produced qualitatively similar effects on whole‐cell currents, suggesting that the impact of Neto1 on the desensitization properties of heteromeric receptors was not subunit dependent. These results provide greater insight into the functional effects of the auxiliary subunit Neto1 on both homomeric and heteromeric KARs. Alteration of the characteristics of desensitization at both sub‐maximal and saturating glutamate concentrations could influence the responsiveness of these receptors to repeated stimuli. As a result, assembly of KARs with the Neto auxiliary subunits could change the kinetic properties of the neuronal response to glutamatergic input.